IMPROVING MOTIVATION AND LEARNING ACHIEVEMENTS WITH VEE DIAGRAM IN SALT HYDROLYSIS MATERIAL AT SENIOR HIGH SCHOOL SUKOMORO - Soekristin Prasetyowati (Universitas Negeri Surabaya, 2018)
This study aims to describe the use of vee diagrams in an effort to increase motivation and learning achievement in Chemistry class XI.A.1 Sukomoro 1 Senior High School in the material of Salt Hydrolysis. This research is a classroom action research (CAR) which is carried out in two cycles, each cycle consisting of the stages of planning, implementation, observation and reflection. The research is a quasi experiment with a quantitative approach. The research design is Postest-Only Control Design. The object of the study was all students of class XI.IPA.1 of Senior High School Sukomoro in the 2015/2016 school year. Data collection techniques use test methods, and observation methods. The results showed that chemical learning using vee diagrams can increase motivation and learning achievement of Chemistry students in class XI.IPA.1 in Salt Hydrolysis material. In cycle 1 the average cognitive value of 71.05 becomes 80 in cycle 2, learning Chemistry using vee diagrams can be carried out well and can improve student learning motivation especially students gain real experience in everyday life.